Dissecting the Contribution of Individual Receptor Subunits to the Enhancement of N-methyl-d-Aspartate Currents by Dopamine D1 Receptor Activation in Striatum - Jocoy, Emily L.; André, Véronique M.; Cummings, Damian M.; Rao, Shilpa P.; Wu, Nanping; Ramsey, Amy J.; Caron, Marc G.; Cepeda, Carlos; Levine, Michael S. (Frontiers in Systems Neuroscience, 2011)
Dopamine, via activation of D1 receptors, enhances N-methyl-D-aspartate (NMDA) receptor-mediated responses in striatal medium-sized spiny neurons. However, the role of specific NMDA receptor subunits in this enhancement remains unknown. Here we used genetic and pharmacological tools to dissect the contribution of NR1 and NR2A/B subunits to NMDA responses and their modulation by dopamine receptors. We demonstrate that D1 enhancement of NMDA responses does not occur or is significantly reduced in mice with genetic knock-down of NR1 subunits, indicating a critical role of these subunits. Interestingly, spontaneous and evoked α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionic acid (AMPA) receptor-mediated responses were significantly enhanced in NR1 knock-down animals, probably as a compensatory mechanism for the marked reduction in NMDA receptor function. The NMDA receptor subunits NR2A and NR2B played differential roles in D1 modulation. Whereas genetic deletion or pharmacological blockade of NR2A subunits enhanced D1 potentiation of NMDA responses, blockade of NR2B subunits reduced this potentiation, suggesting that these regulatory subunits of the NMDA receptor counterbalance their respective functions. In addition, using D1 and D2 receptor EGFP-expressing mice, we demonstrate that NR2A subunits contribute more to NMDA responses in D1-MSSNs, whereas NR2B subunits contribute more to NMDA responses in D2 cells. The differential contribution of discrete receptor subunits to NMDA responses and dopamine modulation in the striatum has important implications for synaptic plasticity and selective neuronal vulnerability in disease states.